The association between calreticulin and glucagon-like peptide-1 expressions with prognostic factors in high-grade gliomas - Baran, Oğuz; Akgün, Mehmet Yiğit; Kayhan, Ahmet; Evran, Şevket; Özbek, Muhammet Arif; Akyoldaş, Göktuğ; Samancı, Mustafa Yavuz; Demirel, Nail; Sönmez, Derya; Serin, Huriye; Koçak, Ayhan; Kemerdere, Rahşan (My University, 2024)
Objective: The aim of this study is to present the expressions of Calreticulin (CALR) and Glucagon-like peptide-1 (GLP-1) in high-grade gliomas and to further show the relation between the levels of these molecules and Ki-67 index, presence of Isocitrate dehydrogenase (IDH)-1 mutation, and tumor grade. Patients and Methods: A total of 43 patients who underwent surgical resection due to high-grade gliomas (HGG) (grades III and IV) were included. The control group comprised 27 people who showed no gross pathology in the brain during the autopsy procedures. Adequately sized tumor samples were removed from each patient during surgery, and cerebral tissues were removed from the control subjects during the autopsy procedures. Each sample was stored at -80°C as rapidly as possible until the enzyme assay. Results: Patients with high-grade gliomas showed significantly higher levels of CALR and significantly lower levels of GLP-1 when compared to control subjects (P = 0.001). CALR levels were significantly higher, GLP-1 levels were significantly lower in grade IV gliomas than those in grade III gliomas (P = 0.001). Gliomas with negative IDH-1 mutations had significantly higher CALR expressions and gliomas with positive IDH-1 mutations showed significantly higher GLP-1 expressions (P = 0.01). A positive correlation between Ki-67 and CALR and a negative correlation between Ki-67 and GLP-1 expressions were observed in grade IV gliomas (P = 0.001). Conclusions: Our results showed that higher CALR and lower GLP-1 expressions are found in HGGs compared to normal cerebral tissues.
Keywords: Calreticulin; Glioma; Glucagon-Like Peptide-1; Surgery; Tumor Immunity